2010
DOI: 10.1111/j.1740-0929.2010.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the addition rates of cellulase or glucose and silage fermentation at different temperatures

Abstract: The influence of the application rates of cellulase preparation and glucose on silage fermentation at different temperatures was studied with the straw of naked barley (Hordeum vulgare L. emand Lam) and guineagrass (Panicum maximum Jacq.). Addition rate of cellulase and glucose, temperature and their interaction had significant effects on pH value, lactic acid content, butyric acid content and propionic acid content of naked barley straw silage and significant effects on all the parameters of guineagrass silag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 11 publications
5
27
0
4
Order By: Relevance
“…However, when the wilting period was prolonged to 12 h in our research, the wilted stylo was significantly higher in NDF content and lower in WSC content than unwilted and 6 h wilted materials. In the LW and HW silages, butyric acid was not detected at either low temperature or high temperature, whereas the NW silage at 30°C contained higher butyric acid content than at other temperatures, which agreed about the result of Zhang et al (1997aZhang et al ( , 2010. In general, good silage depends on reasonable moisture contents of material.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, when the wilting period was prolonged to 12 h in our research, the wilted stylo was significantly higher in NDF content and lower in WSC content than unwilted and 6 h wilted materials. In the LW and HW silages, butyric acid was not detected at either low temperature or high temperature, whereas the NW silage at 30°C contained higher butyric acid content than at other temperatures, which agreed about the result of Zhang et al (1997aZhang et al ( , 2010. In general, good silage depends on reasonable moisture contents of material.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, Zhang et al (1997b) reported that storage temperature had no significant effect on pH, acetic acid and butyric acid contents of corn silage, while it had significant effect on all the fermentation parameters of guineagrass silage. Guineagrass silage kept at 30°C had less lactic acid and higher pH value than that kept at 40°C (Zhang et al 1997b(Zhang et al , 2010. Tjandraatmadja et al (1991) and Mitsuaki et al (1997) found lower butyric acid content or lower pH value at high temperature in their experiments.…”
Section: Introductiona Sj_873 549553mentioning
confidence: 93%
“…Due to the low water soluble carbohydrates (WSC) content in straw, tremendous efforts have been made to improve fermentation quality and nutritive value of straw silage by supplying fermentation substrate directly or indirectly (LI et al, 2010, ZHANG et al, 2010. Molasses has been proven to be an effective silage additive by promoting lactic acid bacteria fermentation, reducing silage pH, discouraging clostridia fermentation and proteolysis, and generally decreasing organic matter losses when applied to crops with low water soluble carbohydrates (WSC) (BOLSEN et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, butyric acid was detected in BSLl added RG silage (2.7 g kg·1 DM), while it was not in other silages. The different results might be caused by different WSC contents and buffering capacity in various treatments [17].…”
Section: Resultsmentioning
confidence: 99%